Developing an Easy Read Version of the Adult Social Care Outcomes Toolkit (ASCOT). Issue 1 (24th October 2016) - Turnpenny, Agnes; Caiels, James; Whelton, Beckie; Richardson, Lisa; Beadle‐Brown, Julie; Crowther, Tanya; Forder, Julien; Apps, Joanna; Rand, Stacey
Abstract : Background: This study reports the experiences of developing and pre‐testing an Easy Read version of the Adult Social Care Outcomes Toolkit (ASCOT) for self‐report by people with intellectual disabilities. Methods: The study has combined survey development and pre‐testing methods with approaches to create accessible information for people with intellectual disabilities. A working group assisted researchers in identifying appropriate question formats, pictures and wording. Focus groups and cognitive interviews were conducted to test various iterations of the instrument. Results: Substantial changes were made to the questionnaire, which included changes to illustrations, the wording of question stems and response options. Conclusions: The process demonstrated the benefits of involving people with intellectual disabilities in the design and testing of data collection instruments. Adequately adapted questionnaires can be useful tools to collect information from people with intellectual disabilities in survey research; however, its limitations must be recognized.